Impacts of environmental factors on arsenate biotransformation and release in Microcystis aeruginosa using the Taguchi experimental design approach. (1st July 2017) - Wang, Zhenhong; Luo, Zhuanxi; Yan, Changzhou; Xing, Baoshan
Abstract: Very limited information is available on how and to what extent environmental factors influence arsenic ( As ) biotransformation and release in freshwater algae. These factors include concentrations of arsenate ( As (V)), dissolved inorganic nitrogen (N), phosphate (P), and ambient pH . This study conducted a series of experiments using Taguchi methods to determine optimum conditions for As biotransformation. We assessed principal effective factors of As (V), N, P, and pH and determined that As biotransformation and release actuate at 10.0 μM As (V) in dead alga cells, the As efflux ratio and organic As efflux content actuate at 1.0 mg/L P, algal growth and intracellular arsenite ( As (III)) content actuate at 10.0 mg/L N, and the total sum of As (III) efflux from dead alga cells actuates at a pH level of 10. Moreover, N is the critical component for As (V) biotransformation in M. aeruginosa, specifically for As (III) transformation, because N can accelerate algal growth, subsequently improving As (III) accumulation and its efflux, which results in an As (V) to As (III) reduction. Furthermore, low P concentrations in combination with high N concentrations promote As accumulation. Following As (V), P was the primary impacting factor for As accumulation. In addition, small amounts of As accumulation under low concentrations of As and high P were securely stored in living algal cells and were easily released after cell death. Results from this study will help to assess practical applications and the overall control of key environmental factors, particularly those associated with algal bioremediation in As polluted water. Graphical abstract: Highlights: Taguchi method was used to select the parameters having the most principal effect. Control factors of N, P, pH, and As (V) were implemented on practical levels in aquatic systems. As (V) was the primary factor to affect As accumulation, As species, and As (V) efflux. Low P along with high N were beneficial to As accumulation in algae. N was a key factor in algal As(V) biotransformation, particularly in As(III) transformation.